A New Experimental Approach for In Situ Damage Assessment in Fibrous Ceramic Matrix Composites at High Temperature. Issue 6 (9th March 2015) - Tracy, Jared; Waas, Anthony; Daly, Samantha; Hsueh, C.‐H.
<x xml:space="preserve">Abstract</x> High‐temperature applications of ceramic matrix composites necessitate a rigorous understanding of the fracture and damage mechanisms that occur under thermomechanical loading, requiring the development of advanced small‐scale characterization approaches. In this work, fiber‐reinforced SiC/SiC tensile specimens were loaded in a scanning electron microscope at 800°C, and full‐field deformation maps at the constituent length scale were generated using digital image correlation (DIC). A colloidal system containing mechanically milled titanium nanopowder, bicine, and water was developed for use as a DIC tracking pattern that is stable at 795°C. The resultant full‐field strain maps provide a constituent level characterization of damage evolution from crack initiation through final fracture. An analysis of strain along fiber lengths indicated that fiber mean strain and standard deviation reached a minimum at fiber fracture. In addition, multiple matrix cracks in the process zone ahead of a notch/crack tip were apparent and could falsely appear as a continuous region of high strain in DIC fields. Relatively large displacement (strain) error was attributed to noise and bias at these small length scales and small strain values, and approaches for mitigating this error are discussed.